Teaching and Learning Statistics in Nigeria with the Aid of Computing and Survey Data Sets from International Organizations - Adenomon, Monday Osagie (Promoting Statistical Practice and Collaboration in Developing Countries, 2022)
Statistics is a discipline that cuts across every field of life to provide solutions to problems that could help in research, decision-making, and policy formulation, which can be facilitated through the new approaches to teaching and learning statistics introduced in this chapter. Achieving effective teaching and learning statistics in developing countries such as Nigeria is possible with the availability of free computing software such as R and free survey data sets from international organization (WHO, United Nations Children's Fund, etc.) websites and using the TEAM (Teach, Examples with real-world data, Attitudinal influence, and Mentoring) framework, which has been proposed and shared in this chapter for teaching and learning statistics in developing countries such as Nigeria. The TEAM framework synchronizes the use of statistical computing and survey data sets from international organization websites. For example, from my teaching experience, both undergraduate and postgraduate students are quick to understand topics in probability when they are taught with real-life data sets and statistical computing.